Attempts to capturing ppb-level elements from sea water with hydrogels. (September 2016) - Hara, Kazuhiro; Fujiwara, Seiya; Fujii, Tetsumasa; Yoshioka, Satoru; Hidaka, Yoshiki; Okabe, Hirotaka
Abstract: Stable energy resource supply is an important subject from the perspective of national security. In this sense, recovering uranium from seawater is important and profitable for the countries of which the land is surrounded by sea and is not endowed with energy resources such as Japan. However, the concentration of uranium dissolved in seawater is extremely low (ppb level) but the total amount of uranium is huge because of the tremendous seawater volume on the Earth. Therefore, in order to promote the efficiency of adsorbents capturing ppb-level uranium from seawater, the authors propose the utilization of hydrogel as a new adsorbent base material. In order to demonstrate the usefulness of the hydrogel for the ppb-level element-adsorption from seawater, the authors have developed the amidoxime incorporated hydrogel and have examined their ppb-level uranium capturing efficiency in the presence of other elements. From the experimental results, a potential for this purpose has been demonstrated by considerably high adsorption functionality. Highlights: Usage of hydrogel is proposed to capture seawater-uranium with higher efficiency. For this purpose, amidoxime-incorporated hydrogels have developed. Their ppb-uranium uptake have been measured in the presence of other elements. The present hydrogel is estimated promising for capturing seawater uranium.